Evaluating the Antihyperalgesic Potential of Sildenafil-Metformin Combination and Its Impact on Biochemical Markers in Alloxan-Induced Diabetic Neuropathy in Rats - Ciprian Pușcașu; Simona Negreș; Cristina Elena Zbârcea; Anca Ungurianu; Emil Ștefănescu; Nicoleta Mirela Blebea; Cornel Chiriță (MDPI AG, 2024)
(1) Background: Globally, about 600 million people are afflicted with diabetes, and one of its most prevalent complications is neuropathy, a debilitating condition. At the present time, the exploration of novel therapies for alleviating diabetic-neuropathy-associated pain is genuinely captivating, considering that current therapeutic options are characterized by poor efficacy and significant risk of side effects. In the current research, we evaluated the antihyperalgesic effect the sildenafil (phosphodiesterase-5 inhibitor)-metformin (antihyperglycemic agent) combination and its impact on biochemical markers in alloxan-induced diabetic neuropathy in rats. (2) Methods: This study involved a cohort of 70 diabetic rats and 10 non-diabetic rats. Diabetic neuropathy was induced by a single dose of 130 mg/kg alloxan. The rats were submitted to thermal stimulus test using a hot-cold plate and to tactile stimulus test using von Frey filaments. Moreover, at the end of the experiment, the animals were sacrificed and their brains and livers were collected to investigate the impact of this combination on TNF-α, IL-6, nitrites and thiols levels. (3) Results: The results demonstrated that all sildenafil-metformin combinations decreased the pain sensitivity in the von Frey test, hot plate test and cold plate test. Furthermore, alterations in nitrites and thiols concentrations and pro-inflammatory cytokines (specifically TNF-α and IL-6) were noted following a 15-day regimen of various sildenafil-metformin combinations. (4) Conclusions: The combination of sildenafil and metformin has a synergistic effect on alleviating pain in alloxan-induced diabetic neuropathy rats. Additionally, the combination effectively decreased inflammation, inhibited the rise in NOS activity, and provided protection against glutathione depletion.